Reliability assessment of miniaturised electromechanical RF relays for space applications. (November 2022) - Marozau, I.; Unterhofer, S.; Berry, M.; Aubry, G.; Gonin, P.; Enquebecq, R.; Dadras, M.; Sereda, O.
Abstract: A test programme was developed for the reliability assessment and evaluation of radiofrequency (RF) miniaturised electromechanical relays (MEMR) as required for space application. The test programme allows to carry out the required qualification of newly designed MEMR device for its use in space as well as in terrestrial applications (e.g. redundancy rings in telecom satellites or 5G technology equipment). It is aligned with the existing ESA standards for the direct current (DC) electromechanical relays. At the same time, the test and evaluation procedures are designed to meet the specific needs and requirements of the RF application domain. The developed test programme was successfully applied for the reliability evaluation of the MEMR developed within the framework of SELECTOR EU project (grant number 821973). The performed failure mode analysis allowed to improve the mechanical robustness of the device to match the qualification requirements. Highlights: Development of miniaturised electromechanical RF relay Reliability of miniaturised electromechanical RF relay for space applications Failure mode analysis for mechanical shock test Lifetime calculation for the RF relay switching operation ESA qualification test programme for the RF electromechanical relay